2014
DOI: 10.1007/s11033-014-3678-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic diversity studies among populations of tea mosquito bug, Helopeltis theivora from Assam, India

Abstract: Multilocus DNA fingerprinting and morphometry were compared to evaluate genetic diversity of tea mosquito bug, Helopeltis theivora Waterhouse (Hemiptera: Miridae). Eighty-one female individuals representing 27 populations of H. theivora from tea plantations of different regions of Assam, India were collected and evaluated. Observation of 12 characters i.e. body length, antennae length, head width, stylet length, thorax width, forewing length, forewing width, hind wing length, hind wing width and length of fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…theivora take in the plant juice from young buds, leaves, fruits and shoots with their piercing-sucking mouthparts 25 . As a consequence, drying up of shoots and fruits can arise from their sucking behavior, which causes more than 25% of crop losses 26,27 . In addition, this pest demonstrates high persistence of populations against stressful environment through strong ability of adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…theivora take in the plant juice from young buds, leaves, fruits and shoots with their piercing-sucking mouthparts 25 . As a consequence, drying up of shoots and fruits can arise from their sucking behavior, which causes more than 25% of crop losses 26,27 . In addition, this pest demonstrates high persistence of populations against stressful environment through strong ability of adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that trichomes did not significantly affect the reduction of Helopeltis damage in tea clones. Helopeltis has long styles measuring 1.5-2.1 mm (Bhau, Mech, Borthakur, Bhuyan, & Bhattacharyya, 2014). Trichomes did not sufficiently prevent a Helopeltis attack in the bottom part of the leaves because tea leaves have trichomes in the bottom part, while Helopeltis attack the upper surface of leaves.…”
Section: Resultsmentioning
confidence: 98%
“…One of these strategies is the PCR-based randomly amplified polymorphic DNA (RAPD), which is a type of polymerase chain reaction where the fragments of DNA are randomly amplified, using short synthetic oligonucleotides of random sequence (Williams et al, 1990). The RAPD marker system has many advantages, including the low cost, little technical demands, and no prior knowledge about DNA sequence (Bhau et al, 2014). Besides, according to Anbalagan et al (2012), RAPD marker system is suitable for studies of population structure because it allows for the detection of polymorphisms in coding and non-coding regions of both nuclear and mitochondrial genomes.…”
Section: Introductionmentioning
confidence: 99%